2015
DOI: 10.1016/j.jbiomech.2015.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the effects of mechanical and osmotic loading on glycosaminoglycan synthesis rate in cartilaginous tissues

Abstract: The glycosaminoglycan (GAG) plays an important role in cartilaginous tissues to support and transmit mechanical loads. Many extracellular biophysical stimuli could affect GAG synthesis by cells. It has been hypothesized that the change of cell volume is a primary mechanism for cells to perceive the stimuli. Experimental studies have shown that the maximum synthesis rate of GAG is achieved at an optimal cell volume, larger or smaller than this level the GAG synthesis rate decreases. Based on the hypothesis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…2). The value of β has been found to be 2.41 for isolated bovine NP cells under osmotic loading (Gao et al, 2015), and this value was also found to work for both bovine NP and AF cells resided within the ECM in this studies.…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…2). The value of β has been found to be 2.41 for isolated bovine NP cells under osmotic loading (Gao et al, 2015), and this value was also found to work for both bovine NP and AF cells resided within the ECM in this studies.…”
Section: Discussionsupporting
confidence: 59%
“…This multiscale mathematical model is based on the cell volume dependent GAG synthesis theory (Gao et al, 2015) that predicts the variation of GAG synthesis rate of a cell under the influence of a mechanical stimulus, and the biphasic theory (Mow et al, 1980) that predicts the tissue deformation of IVD under mechanical loading. These two theories describe two different (biological and mechanical) phenomena at different scale levels (cell level and tissue level) were coupled together with a cell-matrix unit approach which establishes a relationship between GAG synthesis rate and local tissue dilatation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations